The Association of Targeted Cell Salvage Blood Transfusion During Cesarean Delivery With Allogeneic Packed Red Blood Cell Transfusions in a Maternity Hospital in China. (September 2018) - Yan, Haiya; Hu, Ling-Qun; Wu, Yun; Fan, Qihui; Wong, Cynthia A.; McCarthy, Robert J.
Abstract : BACKGROUND: Autologous transfusion of intraoperative cell salvage blood may be a potential method to decrease the need for allogeneic packed red blood cell transfusions after cesarean delivery, although there are limited data on the benefits of this method. This study evaluated the implementation of targeted intraoperative cell salvage during cesarean delivery in women at increased risk for hemorrhage at the Women's and Children's Hospital in Ningbo, China. METHODS: All women who underwent cesarean delivery >28 weeks of gestation were included in the study. The period before intraoperative cell collection (October 1, 2010, to August 31, 2012, n = 11, 322) was compared with the postimplementation period (September 1, 2012, to June 30, 2015, n = 17, 456) using an interrupted time series analysis. In the postimplementation period, women suspected to be at increased risk of the need for a blood transfusion (1604, 9.2%) underwent intraoperative cell salvage collection. The primary outcomes were the monthly rate of allogeneic packed red blood cell use and the incidence of clinical manifestation of acute blood transfusion reactions. RESULTS: The mean (standard deviation) estimated monthly allogeneic packed blood cell transfusion rate at the end of the 57-month study was 2.2% ± 0.7% with the implementation compared with 2.7% ± 0.9% without, difference −0.5%, 95% CI, −1.4% to 0.3%; P = .22. The mean number of allogeneic units transfused per patient was 4.1 ± 0.4 units with implementation and 3.9 ± 0.9 units without, difference 0.2, 95% CI, −1.7 to 1.1 units; P = .69. Intraoperative cell salvage blood was reinfused in 757 (47%) and wasted in 847 (53%) cases. The monthly intraoperative allogeneic packed red blood cells use rate was lower after implementation (difference −0.7%, 95% CI, −0.1% to −1.4%; P = .03); however, the monthly postpartum allogeneic packed red blood cell use rate was unchanged (difference −0.2%, 95% CI, −0.4% to 0.7%; P = .56). The clinical manifestation of acute blood transfusion reactions rate was unchanged (difference −2%, 99% CI, −9% to 5%; P = .55) between the periods. CONCLUSIONS: Our findings suggest that targeted intraoperative cell salvage in women undergoing cesarean delivery was associated with less allogeneic blood exposure in the operating room, but not in the postoperative period. Intraoperative cell salvage in targeted cesarean deliveries was not associated with a lesser allogeneic red blood cell exposure over the hospital admission period. The lack of adverse events associated with intraoperative cell salvage supports the safety of intraoperative cell salvage in cesarean delivery.